2014
DOI: 10.1016/j.mrfmmm.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 overexpression in mouse lungs triggers systemic genotoxicity in peripheral blood

Abstract: Asthma is a common heterogeneous disease with both genetic and environmental factors that affects millions of individuals worldwide. Activated type 2 helper T cells secrete a panel of cytokines, including IL-13, a central immune regulator of many of the hallmark type 2 disease characteristics found in asthma. IL-13 has been directly implicated as a potent stimulator of asthma induced airway remodeling. Although IL-13 is known to play a major role in the development and persistence of asthma, the complex combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…44 The observation that asthma is associated with gH2AX foci is consistent with the induction of DSBs and possibly stalled replication forks. 45 Our results have extended those reported by Chapman et al, 46 which showed that asthma could induce systemic genotoxicity, as measured based on micronucleus formation and protein nitration in peripheral blood. Results described here indicate that HDM induces DNA damage and repair in human bronchial epithelial cells and in lungs of mice and human subjects with asthma.…”
Section: Discussionsupporting
confidence: 89%
“…44 The observation that asthma is associated with gH2AX foci is consistent with the induction of DSBs and possibly stalled replication forks. 45 Our results have extended those reported by Chapman et al, 46 which showed that asthma could induce systemic genotoxicity, as measured based on micronucleus formation and protein nitration in peripheral blood. Results described here indicate that HDM induces DNA damage and repair in human bronchial epithelial cells and in lungs of mice and human subjects with asthma.…”
Section: Discussionsupporting
confidence: 89%
“…Further research may benefit from the inclusion of a broader panel of markers of systemic inflammatory activity that are known to be released from senescent cells and a better characterization of DNA damage in treatment-exposed cancer survivors using markers like hOGG1 to discriminate between oxidative and non-oxidative damage. 37 Host factors may also play an important role in determining the extent and duration of the damage seen in treatment-exposed cancer patients and associated inflammation, and further examination of patient-specific variability, such as genetic variants (e.g., hOGG1 variant S326C-OGG1 38 ) that influence DNA repair capacity is warranted. Similarly, telomere length has also been found to be partially determined by genetic factors and inheritance, 39 , 40 and future work should consider the role this might play.…”
Section: Discussionmentioning
confidence: 99%
“…Il-13 is another pro-inflammatory cytokine that plays a central role in the pathogenesis of pulmonary fibrosis [25] and asthma [26,27]. It regulates eosinophilic inflammation, mucus secretion, and airway hyperresponsiveness and is considered as a key regulator of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates eosinophilic inflammation, mucus secretion, and airway hyperresponsiveness and is considered as a key regulator of the extracellular matrix. Substantial up-regulation of Il-13 in mice exposed to protons+ 56 Fe suggests gross immunological repercussions in the lung tissue, as overexpression of Il13 alone is sufficient to induce non-allergic asthma [27]. Furthermore, it has been shown that Il13 can induce fibrosis independently of Tgfβ1 [28].…”
Section: Discussionmentioning
confidence: 99%